Padrão vocal de reconhecimento específico em Troglodytes musculus (Aves: Passeriformes: Troglodytidae) no Rio de Janeiro - Esteves, Carlos Bizarro (2005)
Individuals House Wrens Troglodytes musculus may be recognized by voice as members of this species despite their songs differ very much from each other. ln this work I described the main features of the song of T. musculus and quantified the variation of some of its acoustic properties, in order to look for those possibly responsible for transmitting that species-specific information. Two very distinct parts may be recognized in this species' song. The first (and significantly longer) part shows biphonated notes, buzzes, dense harmonics and chaotic segments, while the second one is composed of trills of tonal notes with variable frequency modulation. Trills varied mainly in respect to frequency range and duration. Intersyllable interval and syllable duration were the less variable features of trills, while the minimum frequency and the variation of the frequency range varied more. Inter-syllable interval was the most conservative parameter also in the first part of songs, followed by the dominant frequency and syllable duration. The rhythm of the trills and their frequency variation over time seem to be related to the coding of species-specific information, whose long-distance transmission may be optimized by the frequency range and greater loudness of trills. Given that the first part of the song is composed of acoustic units less well suited for long-distance propagation, it is probably only or mainly used for short-distance communication between males or between males and females. New research is still needed to test some of these hypotheses on the acoustic communication of the House Wren.